Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Konsumen yang di Mediasi Oleh Minat Beli - Novia Ari Sandra; Ni Wayan Deriani; Ponisih Panjaitan (UNHI Press, 2023)
Fashion retail that is growing rapidly today is Hennes & Mau itz (H & M). H&M's rating experienced two downgrades in 2019 and in 2020 experienced another three downgrades. It is therefore important for H&M to pay attention to the factors influencing purchasing decisions. The purpose of this study is to determine the effect of product quality on buying interest, then to determine the influence of product quality and buying interest on purchasing decisions, and to determine the influence of product quality on purchasing decisions mediated by buying interest in H&M Products in Bali. This research method uses quantitative methods. The population in this study is consumers of H & M Products. The number of samples in this study is as many as 100 consumers of H & M Products. Data analysis techniques are path analysis, t test, mediation influence test. The results of the analysis show: (1) There is a positive and significant influence of product quality on buying interest; (2) There is a positive and significant influence of buying interest on purchasing decisions; (3) There is a positive and significant influence of product quality on purchasing decisions; (4) Purchase interest can mediate product quality against purchasing decisions. This means that if H&M is able to provide high product quality for consumers, then the quality of these products will be able to increase consumer buying interest and ultimately consumer purchasing decisions on H&M products will increase.